2015
DOI: 10.1089/scd.2014.0484
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Reactive Oxygen Species in Mesenchymal Stem Cell Adipogenic and Osteogenic Differentiation: A Review

Abstract: Mesenchymal stromal cells (MSCs) are promising candidates for tissue engineering and regenerative medicine. The multipotent stem cell component of MSC isolates is able to differentiate into derivatives of the mesodermal lineage including adipocytes, osteocytes, chondrocytes, and myocytes. Many common pathways have been described in the regulation of adipogenesis and osteogenesis. However, stimulation of osteogenesis appears to suppress adipogenesis and vice-versa. Increasing evidence implicates a tight regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
439
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(459 citation statements)
references
References 143 publications
(168 reference statements)
14
439
2
4
Order By: Relevance
“…These infiltrated immune cells in BM secret more proinflammatory factors and together contribute to an inflammatory microenvironment. It is known that proinflammatory cytokines such as TNFα and IL-1 also stimulate ROS generation through mitochondrial and NADPH oxidase system [44]. Therefore, oxidative stress and inflammation together promote a positive feedback loop that characterizes the pathological microenvironment of aged BM (Fig.…”
Section: How Pathological Conditions Change the Bm?mentioning
confidence: 99%
“…These infiltrated immune cells in BM secret more proinflammatory factors and together contribute to an inflammatory microenvironment. It is known that proinflammatory cytokines such as TNFα and IL-1 also stimulate ROS generation through mitochondrial and NADPH oxidase system [44]. Therefore, oxidative stress and inflammation together promote a positive feedback loop that characterizes the pathological microenvironment of aged BM (Fig.…”
Section: How Pathological Conditions Change the Bm?mentioning
confidence: 99%
“…High ROS levels in stem cells cause damage and dysfunction, but a low basal level of ROS is necessary for maintaining cellular proliferation, differentiation, and survival. 193,194 Multiple studies using different disease models [195][196][197][198] demonstrated that MSC could exert an antioxidative effect leading to a decrease in severity of organ injury. 199 This effect is primarily regulated through secretion of soluble factors, which prevent ROS accumulation through enhanced scavenging and antioxidant upregulation.…”
Section: Inactivation Of Oxidative Stressmentioning
confidence: 99%
“…31 In particular, excessive ROS cause damage to MSCs, whereas low levels of ROS enhance osteogenesis of MSCs. 32 To determine the viability of hADMSCs treated with chitosan-conjugated AuNPs, cell viability assays were performed for 72 hours in a growth medium that did not contain osteogenic-inducing substances ( Figure 2A). As shown in Figure 2A, chitosan-conjugated AuNPs had no effect on the cell viability of hADMSCs at a concentration of up to 10 ppm.…”
Section: Effect Of Chitosan-conjugated Aunps On Hadmsc Viability Andmentioning
confidence: 99%